An optimal model of long-term post-stroke care - Sarzyńska-Długosz, Iwona (Frontiers in Neurology, 2023)
Stroke is one of the biggest and still growing public health-care challenges. The burden of stroke is prominent for individual person as well as for general population. Good quality od stroke care is necessary to reduce negative impact of stroke. In the paper were combined information from systematic reviews, guideline documents and research literature on stroke care and rehabilitation facilities for patients after discharge from stroke units in aim to propose the best standard for organization of long-term post-stroke care. It also points to the unmet needs of post-stroke patients in terms of early diagnosis and proper comprehensive therapy.